Tantangan Pendidikan Multikultural Dalam Era Globalisasi Di Indonesia - Ilyas Rifa'i (ISLAMICA, 2015)
Indonesia is a very diverse country. Its diversity can be seen from the many islands, ethnicity, culture, language and religion. Plurality is then led to the motto Unity in Diversity. Indonesia is a country of multi-ethnic, multi-cultural and multi-religious. This diversity, on the one hand is a blessing, because it actually reflects the diversity of the wealth of cultural treasures. No wonder if Satjipto Raharjo finds that Indonesia is a very complete laboratory and promising to investigate in the field of social sciences and humanities. But on the other hand, diversity is also great potential for growing proliferation of conflicts, particularly if diversity is not able to run properly. To build a society that recognizes and appreciates differences is required an education process. Herein lies the importance of multicultural education. Multicultural education is becoming very strategic to be able to manage diversity creatively. Multicultural education should be a process of internalization of the values ​​of multiculturalism itself in educational institutions.